OPTIMIZATION OF TEACHING METHODS IN SPORTS CLASSES WITH STUDENTS WITH VISUAL IMPAIRMENTS - Mariana Albert; Evald Albert (Scientific Publishing House. NSA Press, 2017)
The motivation for conducting the present research is the creation of kinesitherapeutic algorithms adapted to visually impaired student so that they can achieve greater autonomy and activity in motor skills during sports classes. The aim of the study is to develop a kinesitherapeutic program to improve the physical fitness of students with visual impairments during their sports classes. Tasks: To explore the peculiarities of the students' adaptation to regular physical workload; To analyze the students' social behavior and attitude within and outside the group; To optimize the methods of teaching sport. The research was done among 105 people (male and female) with major Vision-impaired Masseurs. The Kinesitherapeutic Program included five successive stages: 1. Improving coordination 2. Training proper breathing. 3. Investigating and practicing Chi gon exercise. 4. Learning and applying yoga exercises. 5. Filling in a questionnaire. The survey shows that 82.86% of students believe the kinesitherapeutic program improves their autonomy and locomotion activity, increases their motor skills and physical fitness. The kinesitherapeutic program is applicable to pupils as well as students with visual disturbances with different majors. For the first time, sports classes combine Chi gong and yoga exercises with static-strength workouts and balance exercises to increase physical activity as well as to prevent and treat clinical conditions associated with visual disturbances.